MODEL PENGEMBANGAN RADIO DBS FM DALAM UPAYA MENCAPAI KEUNGGULAN KOMPETITIF DI FAKULTAS DAKWAH UNIVERSITAS IBRAHIMY - Imam Syafii (As-Sidanah, 2020)
The output of the DBS FM Radio program should be based on a vision and mission that is generally required to fulfill the trilogy rules of the broadcast radio function, which is to inform, educate and entertain. The three do not stand alone because they are a unitary target. The vision and mission of DBS FM Radio broadcast cannot be separated from the vision and mission of the Da'wah Faculty of Ibrahimy University as a logical consequence in its position as campus radio, student practicum radio. The flow that must be understood by DBS FM Radio broadcasting organizers should be different from commercial radio broadcasting. The communication pattern and broadcast material must be able to meet the target audience of the audience, namely students, students and the community around the Salafiyah Syafiiyah Islamic Boarding School Sukorejo Situbondo. Efforts must be made to obtain a goal setting with the SMART formula that is expected to be able to create changes from existing conditions to better conditions with HR qualifications that have the ability to announce skills, operating skills and attitude skills, namely by assisting the development model as a replicable alternative effort to achieve competitive advantage.